STRATEGI PENINGKATAN KOMPETENSI PROFESIONAL GURU - Khudori, Saed Al; Ginting, Rahmadani Ftri (Cahaya Ilmu Bangsa Institute, 2024)
Abstract This research is a qualitative study conducted through a literature review, focusing on various references related to strategies for enhancing teachers' professional competence. The teaching profession requires various professional qualifications. The quality of education largely depends on the quality of teachers. Only qualified teachers can perform their duties effectively. The primary responsibility of teachers is to educate the nation comprehensively, develop the personalities of Indonesian individuals, and cultivate scientists and skilled professionals. A qualified teacher is one who meets the personal criteria and possesses technical skills in teaching. This paper will discuss various strategies needed to improve teachers' professional competence.